The Influence of Good Corporate Governance on Company Value in Registered State-Owned Companies on the Indonesian Stock Exchange - Kurniawan, Rhesi; Abidin, Zaenal (PT. Riset Press International, 2025)
One of the company's goals is to increase the welfare or maximize the wealth of shareholders through increasing company value. Company value can be influenced by several factors, including the number of company assets and how long the company has been established and also through good corporate governance. The internal elements of good corporate governance used in this research include institutional ownership and managerial ownership. Sampling using non-probability sampling obtained a sample of 20 companies so that the research data amounted to 100. The data collection technique used documentation from financial reports published on the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The analysis techniques used are descriptive analysis, classical assumption test, panel data regression model, panel data regression analysis, partial test (t test), simultaneous test (f test), and coefficient of determination test (r2). The results of this research indicate that institutional ownership has a significant influence on company value. Managerial ownership has a significant and influential effect on company value. Then overall institutional ownership and managerial ownership influence company value.